THE ‘GOODS’ CONUNDRUM: THE QUESTION OF VALUE IN MOLDOVAN TRANSNATIONAL PARCEL-SENDING PRACTICES - Caracentev, Sanda (Economy and Sociology, 2024)
Informal transnational exchanges continue to attract the interest of migration scholars. Recent developments in Moldova following the Ukrainian refugee crisis warrant more discussions around the value of such exchanges, particularly in relation to informal provisions of aid. Building on theoretical perspectives on remittances, value and sociality, this article shows that parcel-sending should be addressed in its socio-economic complexity beyond the financial and legislative implications of transporting ‘goods.’ Using ethnographic examples of Moldovan parcel-sending from two fieldworks based on semi-structured interviews and participant observation, the article discusses what parcel-senders and receivers consider ‘valuable’ about this practice, both in the context of everyday transnational life and the Ukrainian refugee crisis in Moldova. Data supporting the ESRC-funded part of this study are available from UK Data Service at https://doi.org/10.5255/UKDA-SN-856679. Data are safeguarded and can be accessed subject to UK Data Service End User Licence Agreement.